S13 Incidence And Risk Factors For The Development Of Hospital Acquired Pneumonia In Older Hospitalised Patients. (10th November 2014) - Burton, LA; Price, RJG; Barr, KE; McAuley, SM; Allen, JB; Clinton, A; Phillips, G; Marwick, CA; McMurdo, MET; Witham, MD
Abstract : Introduction and objectives: Older people are at risk of hospital-acquired pneumonia (HAP). Few data exist on the incidence or risk factors for HAP in non-intensive care patients. Our aim was to determine the incidence and key risk factors for HAP in a sample of older people. Methods: A prospective survey of people >65 years admitted to Acute Medical, Medicine for the Elderly and Orthopaedic wards in NHS Tayside (Dundee, UK) over a 12 month period. HAP was defined in accordance with the European and Scottish National Prevalence Survey of Healthcare Associated Infection and Antimicrobial Prescribing, June 2011. Key analyses included: incidence of case-defined HAP, risk factors for development using Cox regression analysis and the percentage of clinically diagnosed HAP that met the diagnostic criteria for case-defined HAP. Results: A total of 1302 patients were included in the survey, 539 (41%) male, and mean age 82 years (SD 8). Median length of hospital stay was 14 days (IQR 20). 157 episodes of HAP were suspected clinically in 143 patients (incidence 10.9%), but only 83 episodes (53% of total) in 76 patients met the diagnostic criteria (incidence 5.8%). Case fatality rate was 29% in patients with confirmed HAP, and 19% in patients with suspected but not confirmed HAP. Risk of HAP increased by 0.3% per day spent in hospital. Swallowing problems were the single most important risk factor; HR 3.7 (95% CI 2.2 to 6.1, p < 0.001). Conclusion: HAP is common but overdiagnosed in older hospitalised patients. Older patients with swallowing problems have a greater risk of developing HAP. Given the high mortality rate, knock on effects on antibiotic use and length of hospital stay, ways of preventing HAP would be of potential importance to health services.